Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Determine the function's value when [tex]\( x = -1 \)[/tex].

[tex]\[ g(x) = x^3 + 6x^2 + 12x + 8 \][/tex]

\begin{tabular}{|c|c|}
\hline
[tex]$x$[/tex] & [tex]$g(x)$[/tex] \\
\hline
-3 & -1 \\
\hline
-2 & 0 \\
\hline
0 & 8 \\
\hline
2 & 64 \\
\hline
3 & 125 \\
\hline
\end{tabular}

A. [tex]\( g(-1) = -3 \)[/tex]

B. [tex]\( g(-1) = 0 \)[/tex]

C. [tex]\( g(-1) = 1 \)[/tex]

D. [tex]\( g(-1) = 27 \)[/tex]


Sagot :

To determine the value of the function [tex]\( g(x) = x^3 + 6x^2 + 12x + 8 \)[/tex] when [tex]\( x = -1 \)[/tex]:

1. Substitute [tex]\( x = -1 \)[/tex] into the function:
[tex]\[ g(-1) = (-1)^3 + 6(-1)^2 + 12(-1) + 8 \][/tex]

2. Now, calculate each term step-by-step:
[tex]\[ (-1)^3 = -1 \][/tex]
[tex]\[ 6(-1)^2 = 6(1) = 6 \][/tex]
[tex]\[ 12(-1) = -12 \][/tex]
[tex]\[ 8 \text{ (constant term)} \][/tex]

3. Add these values together:
[tex]\[ g(-1) = -1 + 6 - 12 + 8 \][/tex]

4. Perform the addition/subtraction:
[tex]\[ g(-1) = -1 + 6 = 5 \][/tex]
[tex]\[ 5 - 12 = -7 \][/tex]
[tex]\[ -7 + 8 = 1 \][/tex]

Thus, the value of the function [tex]\( g(x) \)[/tex] when [tex]\( x = -1 \)[/tex] is:
[tex]\[ g(-1) = 1 \][/tex]

So, the correct answer is:
[tex]\[ g(-1)=1 \][/tex]